2010
DOI: 10.1515/jbcpp.2010.21.2.107
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antioxidant and Hypolipidemic Effect of Cardiospermum halicacabum Leaf Extract in Streptozotocin-Induced Diabetic Rats

Abstract: In this study we investigated the antioxidant and antihyperlipidemic of an ethanolic leaf extract of Cardiospermum halicacabum (CHE) in plasma and tissues of streptozotocin (STZ)-induced diabetic rats. The plasma and tissue concentrations of thiobarbituric acid reactive substances (TBARS) and lipid hydroperoxide were significantly elevated in STZ diabetic rats. CHE administration decreased TBARS and lipid hydroperoxide levels. The plasma vitamin E level increased and the vitamin C level decreased. The reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Streptozotocin selectively destroys the pancreatic β cells, reduce their activity, and cause diabetes [18]. In the present study, significant weight loss was observed in the diabetic group in addition to an improvement in the weight of rats in the diabetic group treated with fraction ZSC-3.…”
Section: Discussionsupporting
confidence: 59%
“…Streptozotocin selectively destroys the pancreatic β cells, reduce their activity, and cause diabetes [18]. In the present study, significant weight loss was observed in the diabetic group in addition to an improvement in the weight of rats in the diabetic group treated with fraction ZSC-3.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, it was observed that there is a reduction in body weight of the STZ induced diabetic rats which may be due to catabolism of fats and protein [33]. The administration of NNSE improve body weight compared to diabetic control rats, which indicates the preventive effect of plants on the degradation of proteins.…”
Section: Effect Of Nnse On Antioxidant Enzymessupporting
confidence: 54%
“…Anti-inflammatory properties of CH have been researched [11], but no clinical trials have been reported so far. Experimental pharmacological studies of CH have shown antioxidant activity [12] analgesic and vasodepressant activities [13], antipyretic activity [14], Antimalarial activity [15], diuretic activity [16], anti-diarrheal activity [17], anti-diabetic activity [18] and anti-ulcer activity [19].…”
Section: Introductionmentioning
confidence: 99%